Optimal conditions for alkaline treatment of alginate extraction from the brown seaweed Sargassum cymosum C. Agardh by response surface methodology - Nogueira, Marcela Tiemi [UNESP]; Chica, Letícia Rustici [UNESP]; Yamashita, Camila [UNESP]; Nunes, Natalie Stephanie Sawada [UNESP]; Moraes, Izabel Cristina Freitas; Branco, Ciro Cesar Zanini [UNESP]; Branco, Ivanise Guilherme [UNESP] (Elsevier, 2022)
Industrial applications of sodium alginate (SA) stimulate extraction processes, resulting in greater productivity. We determined the effects of pH, temperature, and extraction time of the alkaline treatment on the yield and viscosity-average molecular weight (Mv) of alginate. The optimal conditions (80 °C, pH 10, 90 min) resulted in a yield of 45.79% and Mv of 207.09 KDa. The pH had the highest effect, whereas the effect of time was negligible. The increase in pH led to an increase in the dynamic viscosity, a reduction in antioxidant capacity, and lighter colored alginates. The optimized alkaline treatment was satisfactory to obtain high SA yields from seaweed. Our results facilitate the improvement of the extractability and physicochemical properties of alginate, reducing the processing time and enabling its widespread use in different industrial sectors.
Keywords: Antioxidant capacity; Box-Behnken design; Rheological behavior; Viscosity-average molecular weight; Yield